An Analysis of Compensation and Communication on Employee Performance at Parkson Center Point Medan - Faisal Amri; Rindi Andika; Ramadhan Harahap (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This research is a quantitative model, and while the respondents in this study are all employees who are in the company Parkson Center Point Medan which amounts to 33 people. The data in this study is primary by using questionnaires and distribution of questionnaires to employees. From the results of research data processing, obtained number 2,426> table 1.69, the conclusion is that the Compensation variable (X1) has a significant positive effect on employee performance. And the results of research data processing, obtained number 3,895> table 1.69 then the conclusion is that the communication variable (X2) has a significant positive effect on employee performance